Fabrication of halloysite nanotubes embedded thin film nanocomposite membranes for dye removal. Issue 38 (11th May 2021) - Ormanci‐Acar, Turkan; Keskin, Basak; Korkut, Sevde; Mutlu‐Salmanlı, Oyku; Turken, Turker; Koseoglu‐Imer, Derya Y.; Demir, Tugba U.; Menceloglu, Yusuf Z.; Unal, Serkan; Koyuncu, Ismail
Abstract: Environmental friendly Halloysite nanotubes (HNTs) are used to fabricate novel nanofiltration membranes by in situ interfacial polymerization of piperazine and trimesoyl chloride. The removal of excess amine solution from the porous support membrane surface is a critical step to obtain defect free active layer. Hereby, two main removal tools for the excess aqueous amine solution; a rubber roll or air knife are compared to fabricate a defect free thin film nanocomposite (TFN) nanofiltration (NF) membrane. Removal by the rubber roll is eventuated more favorable than air knife in terms of the reproducibility of NF membranes by comparing salt rejections. By determining the removal step of excess amines, various HNTs concentrations are used to fabricate NF membranes and, these membranes are tested with salt and dye solutions at various pH and temperature ranges. R2 membrane (containing 0.02% [w/v] HNTs) performs the best flux results beside higher rejections of MgSO4 (93.0%) and dye (99.5%). To evaluate the extreme conditionals, further performance tests such as pH and temperature resistance are also performed for R2 membrane. Considering the performances of R2 membrane, HNTs can be demonstrated for tailoring the balance between flux and separation performance of NF membranes. Abstract :